Metafluidic metamaterial: a review. Issue 1 (1st January 2018) - Zhang, Wu; Song, Qinghua; Zhu, Weiming; Shen, Zhongxiang; Chong, Peter; Tsai, Din Ping; Qiu, Chengwei; Liu, Ai Qun
Abstract: Metafluidic metamaterial is a metamaterial the optical response of which is dependent on fluid contributed metamolecules. The dependence originates either from a fluid background coupling to the metamolecule or from the resonance in a liquid structured metamolecule. Different liquid materials including water, liquid crystal, and liquid metals are applied to realize the metafluidic metamaterial. Sophisticated technologies like electric bias and microfluidic system have been used for active control of metafluidic metamaterials which provide a new platform for electromagnetic wave manipulation and metadevice realization. The liquid background and significant tunability of the metafluidic metamaterial promise numerous applications, such as material sensing, bio-detection, energy harvesting, and imaging, just to name a few. Abstract :